Resolving the confused identity of Frankliniella panamensis (Thysanoptera: Thripidae) - Gunawardana, Disna N.; Li, Dongmei; Masumoto, Masami; Mound, Laurence A.; O’donnell, Cheryle A.; Skarlinsky, Thomas L. (Zootaxa, 2017)
Morphological and molecular characters are provided for distinguishing two similar species of Frankliniella that are commonly found by quarantine authorities in international shipments of horticultural produce, particularly from Colombia where panamensis and occidentalis co-exist in greenhouses.